2021
DOI: 10.1039/d0cc06518h
|View full text |Cite
|
Sign up to set email alerts
|

Low-spin 1,1′-diphosphametallocenates of chromium and iron

Abstract: We report two low-spin diphosphametallocenates [K(2.2.2-crypt)][M(PC4Me4)2] (M = Cr, Fe) and propose structural features that allow spin-control in 3d metallocenates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…The EPR spectra of 2a and 2b distinctly differ from the data obtained for "ferrocene-substituted radical anions," which exhibit narrow signals with well-resolved 1 H couplings and symmetry for the center of the spectra. 16 Similar to other low-spin Fe I complexes 56 including 1,1-diphosphaferrocenate, 20 the slightly rhombic spectra of 2a and 2b with comparatively wider and anisotropic signals are consistent with iron d-orbital character of the S = 1/2 ground state. We also performed 57 Fe Mössbauer spectroscopy of each compound in benzene or toluene solutions (Figure 3b).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The EPR spectra of 2a and 2b distinctly differ from the data obtained for "ferrocene-substituted radical anions," which exhibit narrow signals with well-resolved 1 H couplings and symmetry for the center of the spectra. 16 Similar to other low-spin Fe I complexes 56 including 1,1-diphosphaferrocenate, 20 the slightly rhombic spectra of 2a and 2b with comparatively wider and anisotropic signals are consistent with iron d-orbital character of the S = 1/2 ground state. We also performed 57 Fe Mössbauer spectroscopy of each compound in benzene or toluene solutions (Figure 3b).…”
Section: Resultssupporting
confidence: 70%
“…[15][16] Based on the fact that their high instability is caused by the dissociation of the cyclopentadienyl ligand, many attempts have been made to synthesize an isolobal structure of ferrocenate stabilized by the introduction of other ligands. [17][18][19][20][21][22][23][24] Astruc et al reported the synthesis of an iron-based sandwich complex [Fe(Cp)(η 6 -C6Me6)] 21 and its derivatives. 22 Tatsumi et al reported [(Cp*)Fe(μ-polyarene)Fe(Cp*)] complexes obtained by the reduction of half-sandwich Fe(II)Cp* compounds using potassium polyarenides.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16] Based on the fact that their high instability is caused by the dissociation of the cyclopentadienyl ligand, many attempts have been made to synthesize an isolobal structure of ferrocenate stabilized by the introduction of other ligands. [17][18][19][20][21][22][23][24] Astruc et al reported the synthesis of an iron-based sandwich complex [Fe(Cp)(η 6 -C6Me6)] 21 and its derivatives. 22 Tatsumi et al reported [(Cp*)Fe(μ-polyarene)Fe(Cp*)] complexes obtained by the reduction of half-sandwich Fe(II)Cp* compounds using potassium polyarenides.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, isolation of 8 and the room‐temperature stable bis‐phospholyl [K(2.2.2‐cryptand)][Fe(PC 4 Me 4 ) 2 ] ( 15 ) [12] leads to the inference that the presence of an appropriate heteroatom in the ring can stabilize unusual oxidation states of the first‐row transition metals. Extensive studies on dicationic and monoanionic ferrocene ions throw light on how controlling the substituents on the C 5 ring as well as choosing appropriate redox environments can afford previously believed to be difficult synthetic targets [5, 10, 12, 13] . Making these anions stable at room temperature will be the next step in this area of research, which does not seem to be too far away.…”
Section: Figurementioning
confidence: 99%